Dari prestasi ke kecemasan: Memahami sindrom impostor di kalangan mahasiswa - Lailiyah, Adhimah (Maliki Interdisciplinary Journal, 2025)
Impostor syndrome is a psychological phenomenon often experienced by high-achieving college students, in which they doubt their own abilities and achievements, and feel that their success is due to external factors, such as luck, rather than the result of personal effort or ability. This study describes the characteristics of impostor syndrome in college students, such as feelings of low self-esteem, unrealistic standards of achievement, and attribution of success to external factors. This phenomenon is influenced by internal factors, including self-doubt and unrealistically high standards, as well as external factors, such as parenting, social pressure, and traumatic events. Its effects range from academic anxiety, procrastination, discomfort in group activities, to serious mental health problems. Various therapeutic approaches, such as cognitive-behavioral therapy, acceptance, and mindfulness, are highlighted as effective methods in overcoming impostor syndrome. With proper understanding and treatment, students can overcome this phenomenon and maximize their academic and personal potential.